PENGARUH QUALITY OF WORK LIFE (QWL), PERSON ORGANIZATION FIT (PO FIT) TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDI PADA BADAN PELAKSANA PENYULUHAN KABUPATEN TEMANGGUNG) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to analyze the influence of the quality of work life and PO Fit on the performance of employees with Organizational Commitment and OCB as mediators in Badan Pelaksana Penyuluhan Kabupaten Temanggung.The method used in sample collection in this study was sensus. Instrument tests used are validity and reliability test, with the criteria of KMO > 0.5, Loading Factor > 0.4 and Cronbach alpha > 0.7, while the model test used is Adj-R2 (coefficient of determination) and F-test (Goodness of Fit). Hypothesis test in this study is regression analysis using the t-test. Hypothesis testing is using t-value of frequency distribution at significance level (α) of 5%. While mediation test is using path analysis.Based on the results, the study can be summarized as follows: (1) QWL has positive influence on Organizational Commitment, (2) PO Fit has positive influence on Organizational Commitment, (3) QWL has positive influence on OCB, (4) PO Fit has positive influence on OCB, (5) Organizational Commitment has positive influence on OCB, (6) QWL has positive influence on performance, (7) PO Fit positively influencing performance, (8) Organizational Commitment has positive influence on performance, and (9) OCB has positive influence on performance. Keywords: Quality of work Life, Person Organization Fit, Organizational Commitment, Organizational Citizenship Behavior, Performance.